Prioritizing vulnerable children: why should we address inequity?. (15th June 2015) - Joshua, P.; Zwi, K.; Moran, P.; White, L.
Abstract: Background: Children and young people from vulnerable population groups, including Indigenous Australians, those in out of home care, those with disabilities and those from refugee families, have difficulties in accessing health services and are at high risk of adverse outcomes, driving population health inequity. Although heterogeneous, these groups face common disadvantage and shared challenges in health service utilization. Aim: This study aims to analyse the demographics of vulnerable child populations in NSW, the rationale for focussing on their health needs and strategies for addressing population health inequity. Methodology: A literature review was undertaken on vulnerable child populations and successful strategies for improving their health outcomes. NSW data on vulnerable children were collated. Findings: Vulnerable children in NSW are estimated to comprise 10–20% of the childhood population. Efforts to improve their health and well‐being can be justified based on child rights, a focus on equity and effectiveness of care, public opinion and the evidence base supporting such interventions. Targeted (subpopulation specific) interventions and delivery of universally applied (population wide) strategies that disproportionately benefit vulnerable populations have been shown to be effective in reducing healthcare disparities. Most available information relates to specific vulnerable population groups. However, some effective strategies and key principles are broadly applicable to the vulnerable child population as a whole. Conclusion: Vulnerable children should be a key focus of healthcare interventions if inequities are to be addressed.